DETERMINAN FRAUD PENGADAAN BARANG/JASA SECARA ELEKTRONIK (E-PROCUREMENT): PADA UNIT KERJA PERANGKAT DAERAH KOTA ADMINISTRASI JAKARTA TIMUR (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2024)
Procurement of goods and services is a significant contributor to corruption in Indonesia, with a high risk of recurring fraud. This study analyzes the impact of committee quality, procurement systems and procedures, and the procurement environment on such fraud. Using primary data from 80 committee members across Regional Work Units (UKPD) in East Jakarta, the data was processed via Smart-PLS 3 using the bootstrapping method at a 0.05 significance level. The results demonstrate that committee quality significantly influences the occurrence of procurement fraud, whereas procurement systems, procedures, and the environment show no significant effect.